Low Complexity Signal Detector for MIMO MCCDMA System for Longer Delay Channel - Rao Challagundla, Papa; Sumithabhashini, P; Chandrasekhar Reddy, P (International Journal of Engineering and Technology, 2018)
In recent years Multiple-input multiple-output (MIMO) Multi carrier code division multiple access (MCCDMA), which combines the advantage of diversities with high spectral efficiency has drawn great attention. In this paper we introduce a novel low-complexity multiple-input multiple-output (MIMO) MMSE detector tailored for MCDCDMA systems, suitable for frequency selective channel. The proposed detector begins with estimation of the minimum mean square error (MMSE) on less reliable symbols followed by iterative de-correlation as post-detection processing for mitigating multiple access interferences. Efficient high-throughput VLSI architecture is used to achieve superior performance compared to the conventional MMSE detectors. The performance of the proposed MMSE detector is close to the efficient maximum likelihood, with significant complexity reduction over higher order constellations. The efficiency of MIMO MCCDMA over high order constellations and its quality retentions are verified through MATLAB BER simulation. Â Â